Statistical analysis of keystroke for solving the computer networks users authenticating problems - Горелов, Д.Ю.; Алексеев, В.О.; Бублик, В.М.; Маслий, Д.В. (Radiotekhnika, 2019)
The analysis of the statistical features of keyboard writing is carried out. The histograms of the absolute values of the digraph time parameters (times of pressing and pause between pressing) do not correspond to the Gaussian distribution. The histograms of the relations of the temporal parameters of digraphs indicate a close to Gaussian distribution, that is, the “randomness” of changes in the parameters of keystroke decreases. Approaches to the construction of complex authentication algorithms that take into account the statistical features of keystroke are proposed.